A MATLAB-Based Virtual Tool for the Electromagnetic Wave Scattering from a Perfectly Reflecting Wedge - Hacivelioglu, Feray; Uslu, M. Alper; Sevgi, Levent (IEEE-Inst Electrical Electronics Engineers Inc, 2011)
A MATLAB-based virtual diffraction too l, using analytical exact as well as well-known high-frequency asymptotic (H FA) techniques, is introduced. Electromagnetic wave scattering from a wedge-shaped object with perfect electrical conductor (PEC) boundaries, under both line-source and plane-wave illuminations, can be automatically analyzed. Effects of various parameters on the reflection, refraction, and diffraction can be investigated. Comparisons among Geometrical Optics (GO), Uniform Theory of Diffraction (UTD), Physical Optics (PO), Physical Theory of Diffraction (PTD), and Parabolic Equation (PE) models are possible through many scenarios and illustrations.
Keywords: Electromagnetic scattering; diffraction; Geometrical Optics; graphical user interface (GUI); exact series; exact integrals; MATLAB simulations; Parabolic Equation Method; Physical Optics; Physical Theory of Diffraction; high-frequency asymptotics; numerical integration; reflection; refraction; shadow diffraction; Uniform Theory of Diffraction; wedge diffraction